An Exploration Of The Transitory Experiences Among Propaedaeutic Seminarians - Jeshrel Martin C. Lloren; Christian M. Canillas; Nelson O. Dago-oc; Carlo C. Onggay; Mary Jane B. Omandam (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2025)
This study investigates the transitory experiences of propaedeutic seminarians and their implications for vocation formation within the Holy Infant Seminary in the Diocese of Pagadian. The inquiry is grounded in the significant understanding of the formative dynamics that occur during the propaedeutic stage, a period foundational to the development of priestly identity yet often underexamined in scholarly discourse. Utilizing the phenomenological approach as delineated by Moustakas (1994), the study engaged a purposive sample of sixth propaedeutic seminarians aged 18 to 23. The researchers served as the principal instruments of data collection, supported by a semi-structured interview guide. Data were analyzed using Moustakas' method of phenomenological reduction and thematic analysis. The findings reveal that the propaedeutic seminarians' initial understanding of the seminary life was predominantly shaped by idealized perception and indirect knowledge acquired through observation of priests, hearing stories, and engaging with fellow seminarians from their parish. This observation is consistent with Bandura's Social Learning Theory, which posits that individuals construct understanding through observation, imitation, and social interaction prior to direct experience. As the propaedeutic seminarians progressed through the propaedeutic stage, they underwent a transformative and meaningful formation process that enhanced their vocational clarity and personal identity. This transformation was facilitated not only through structured seminary programs but also through sustained interpersonal relationships with seminary formators and fellow seminarians, reinforcing the significance of social learning mechanisms. Furthermore, despite encountering various challenges such as personal challenges and adjustment to seminary life, the propaedeutic seminarians exhibited resilience by employing personal spiritual practices and relying on the seminary community for support systems. These coping strategies underscore the seminary's dual role as both a space of spiritual formation and a social learning environment. Overall, the study contributes to a deeper understanding of the formative processes that underpin priestly development, emphasizing the need for integrative and relational approaches in seminary formation.